Respuesta :

Answer:

Below

Step-by-step explanation:

1. 3x+9=5

2.  3x+9-9=5-9

3. 3x=-4

5. 3x/3=-4/3

6. -4/3

7. -1 1/3

Answer:

The answer is -4/3 or - 1 1/3

Step-by-step explanation:

3x+9= 5

    -9    -9

3x = -4

 /3    /3

Y= -4/3 or [tex]-1\frac{1}{3}[/tex]

Step 1: Add subtract 9 to both sides because you want to cancel out the 9 so you do the opposite of what is say's. For example, if it says 3x-9 add 9 or 3x+9 subtract 9 from both sides.

Step 2: Add subtract 9 to 5 which would be -4. So you should have 3x= -4 now

Step 3: Since you're "multiplying" 3 to x you're going to divide 3 to get Y by itself. So 3/3 cancels out and now you're left with y

Step 4: Divide 3 from -4 and you get -4/3

Let me know if you have any questions and I hope this helps :)

ACCESS MORE